pBFK, a new thermosensitive shuttle vector for Streptococcus pyogenes gene deletion by homologous recombination - S. Boukthir; P. Gaudu; A. Faili; S. Kayal (Heliyon, 2023)
Streptococcus pyogenes, or Group A Streptococcus (GAS), is a major human pathogen for which genetic manipulation remains an ongoing challenge. We created a new temperature-sensitive plasmid pBFK expressing spectinomycin resistance adapted to homologous recombination procedure to perform a complete gene deletion in GAS. Herein the mutagenesis strategy with pBFK was performed in a highly virulent GAS emm3 genotype.